1976
DOI: 10.1029/ja081i001p00199
|View full text |Cite
|
Sign up to set email alerts
|

A statistical study of the upstream wave boundary outside the Earth's bow shock

Abstract: The forward boundary of the upstream wave region ahead of the earth's bow shock is located statistically by using combined field and plasma data from a single spacecraft, Heos 1. Interpreting the wave as arising from reflected protons traveling upstream with effective velocity V∥ = pV along the interplanetary field, where V is the solar wind bulk speed, we find that the overall average boundary corresponds to a velocity V∥ ≈ 2V for protons reflected from the daylight sector of the bow shock. More refined parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

1976
1976
2015
2015

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 14 publications
0
22
0
Order By: Relevance
“…The onset of waves in coincidence with large IMF rotations would be in conflict with the quasi‐steadiness condition and therefore might lead to an incorrect identification of the boundary. An early study on the UWFB by Diodato et al [] using magnetic field data from Heos‐1 shows that the boundary is strongly dependent upon the cone angle θ B x , the angle between the IMF direction and the trueboldx̂gse axis. However, the low‐resolution magnetic data (48 s) used in this work‐induced significant uncertainties on the boundary crossings.…”
Section: Introductionmentioning
confidence: 99%
“…The onset of waves in coincidence with large IMF rotations would be in conflict with the quasi‐steadiness condition and therefore might lead to an incorrect identification of the boundary. An early study on the UWFB by Diodato et al [] using magnetic field data from Heos‐1 shows that the boundary is strongly dependent upon the cone angle θ B x , the angle between the IMF direction and the trueboldx̂gse axis. However, the low‐resolution magnetic data (48 s) used in this work‐induced significant uncertainties on the boundary crossings.…”
Section: Introductionmentioning
confidence: 99%
“…according to Diodato et al (1976). This implies that the paths of particles a little below I keV were coincident with the boundary of the wave foreshock.…”
Section: Page Gl10mentioning
confidence: 91%
“…The linking of diffuse ions, quasi-parallel structure, and upstream waves is supported by a simple calculation which at the same time relates the waves to the low, rather than the high, end of the backstreaming ion spectrum. T'e parameter p used in former studies to characterize the foreshock boundary Diodato et al, 1976) can be found in terms of the guiding center energy of an observed return proton: Table 1. In that case, the 1 keV foreshock boundary was tangent close to the subsolar point of curve C, where p z1.6…”
Section: Page Gl10mentioning
confidence: 99%
See 1 more Smart Citation
“…Using the method sketched by Diodato et al (1976), we have checked whether the presence or absence of backstreaming ions was consistent with the observed direction of the interplanetary magnetic field. As shown in Figure 10, the agreement turned out to be very satisfactory.…”
Section: Outward Flows Upstream Of the Bow Shockmentioning
confidence: 99%